2009
DOI: 10.1007/978-3-211-99373-6_11
|View full text |Cite
|
Sign up to set email alerts
|

Present State of Microneurosurgery of Cerebral Arteriovenous Malformations

Abstract: Microneurosurgical excision is known to be the definitive treatment for brain arteriovenous malformation (AVMs). The most important factors governing the operability of an AVM are location, size, age of the patient, and the neurosurgeon's and team's experience. We present in this review the surgical experience of the senior author (JH) in microneurosurgical treatment of brain AVMs. This consists of the following steps: (1) accurate preoperative embolization; (2) optimal selection of the surgical approach; (3) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 24 publications
1
19
0
3
Order By: Relevance
“…The endovascular armamentarium has advanced progressively so as, nowadays, it is considered to be the first line of defense against most complex and critical vascular pathologies. With specific regard for the treatment of IFA, or infectious aneurysms, endovascular procedures, including covered stent reconstruction, coil embolization, and parent vessel occlusion were progressively proposed and increasingly adopted to address the challenges related to the absence of a proper aneurysmal neck [3,[13][14][15][16]18,[21][22][23][24][25][26]. Nevertheless they are not always technically feasible [13,23].…”
Section: Discussionmentioning
confidence: 99%
“…The endovascular armamentarium has advanced progressively so as, nowadays, it is considered to be the first line of defense against most complex and critical vascular pathologies. With specific regard for the treatment of IFA, or infectious aneurysms, endovascular procedures, including covered stent reconstruction, coil embolization, and parent vessel occlusion were progressively proposed and increasingly adopted to address the challenges related to the absence of a proper aneurysmal neck [3,[13][14][15][16]18,[21][22][23][24][25][26]. Nevertheless they are not always technically feasible [13,23].…”
Section: Discussionmentioning
confidence: 99%
“…These results should reinforce the importance of innovative endovascular strategies to make large AVMs amenable to subsequent curative surgical or radiosurgical therapy. 34,35 The highly experienced group of Saatci et al reported their extensive experience with endovascular embolization of 350 AVMs with Onyx Liquid Embolic Material (ev3) with a slow ''staged'' reflux technique. 11 They reported a remarkable 51% angiographic obliteration rate for endovascular therapy alone with permanent morbidity and mortality rates of 7% and 1.4%, respectively.…”
Section: Arteriovenous Malformationsmentioning
confidence: 99%
“…It is generally accepted that the risk of surgery is low (<10%) in Spetzler-Martin (SM) grade 1 and 2 lesions [68][69][70][71]. Spetzler-Martin grade 3 AVMs are a heterogenous group, and complication rates depend largely on the morphology of these lesions, with some having a risk profile similar to that of small (SM grade 1 & 2) AVMs, and some having a risk profile similar to that of large (SM grade 4 & 5) AVMs [72][73][74].…”
Section: Prognosismentioning
confidence: 99%